Women and small-scale irrigation: A review of the factors influencing gendered patterns of participation and benefits - Bryan, Elizabeth; Lefore, Nicole (International Food Policy Research Institute, 2021)
Small-scale irrigation is expanding rapidly in parts of the world, especially sub-Saharan Africa, offering smallholder farmers an opportunity to improve their livelihoods, diets, and resilience to climate change among other benefits. Growing research focuses on the potential for small-scale irrigation to offer a pathway for women’s empowerment, yet the factors conditioning the relationship between small-scale irrigation and women’s empowerment are not well understood. The evidence tends to be scattered across context-specific case studies that focus on targeted outcomes, without distinguishing between technology types, scales, or approaches to irrigation systems or technologies. This paper synthesizes the issues related to gender and small-scale irrigation using a conceptual framework that highlights the linkages between elements of women’s empowerment and small-scale irrigation. Because gendered dynamics with small-scale irrigation play out differently depending on the scale of irrigation and the technologies used, this paper applies the framework to examine case studies across a typology of small-scale irrigation systems. The case studies cover a range of farming and livelihood systems in which women’s roles and gender relations vary, highlighting the importance of the opportunity structure or context in which irrigation takes place. This paper then draws lessons on the various ways in which small-scale irrigation, gender relations, and women’s empowerment interact and highlights areas where research gaps remain.